The Allergenic Potency of Japanese Hop Pollen Is Increasing With Environmental Changes in Korea - Jin, Hyun Jung (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2013)
PURPOSE: The sensitization rate to Japanese Hop (Hop J) in respiratory allergy patients has increased in recent years in Korea. We evaluated changes in the allergenic potency of Hop J pollen collected in 1998 and 2009. METHODS: Thirty-five patients with allergic rhinitis and/or asthma were enrolled. Group I included 21 subjects sensitized to Hop J at an initial visit and group II included 14 subjects who developed a new sensitization. Hop J pollens were collected in 1998 and 2009 (98 and 09 extracts) and both urban and suburban environments (urban and suburban extracts). Serum specific IgE levels to Hop J pollen extracts were compared using an enzyme-linked immunosorbent assay (ELISA). IgE binding components were compared by IgE immunoblot analysis. RESULTS: Serum specific IgE levels to the 09 and urban extracts in both groups increased significantly compared to those of the 98 and suburban extracts. IgE immunoblot demonstrated that the major 10 kDa allergen was intensified in group I, while it was newly generated in group II with additional components ranging from 12-95 kDa. When the 98 and 09 extracts were compared, intensification of the major allergen of 09 extract had occurred in both groups. The IgE binding components of the urban extract was stronger than those of suburban one. CONCLUSIONS: The allergenic potency of Hop J pollen may be increased with environmental changes.